THE FIGURATIVE LANGUAGE IN LANA DEL REY’S SONGS BASED ON TROPICO VIDEO - Noviani, Stella; Bram, Barli (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2021)
Figurative language is a form of communication that creates a memorable impact on the listener through a certain context. To create meaningful impacts in communication, people use figurative language in songs. This paper aimed to explore the figurative language used in the ‘Tropico’ video, which consists of three songs, namely “Body Electric,” “Gods and Monsters,” and “Bel Air” and to examine the contextual meanings of the three songs. The data were collected from the lyrics of the three songs. The data were analyzed through a qualitative descriptive method. The results showed that the types of figurative language that were used in the three songs  were metaphors, similes, personifications, hyperboles, alliterations, metonymies, oxymorons, allusions, repetitions, symbols, imageries, and apostrophes. The use of figurative language in the songs is relatable to the theme of the whole short music video.